Effects of consecutive days of matchplay on maximal hip abductor and adductor strength in female field hockey players - Violeta Sánchez-Migallón; Álvaro López-Samanes; Juan Del Coso; Archit Navandar; Per Aagaard; Víctor Moreno-Pérez (BMC, 2022)
Abstract Background The purpose of this study was to examine the effects of two competitive field hockey matches, played on consecutive days, on maximal isometric hip adductor and abductor strength, wellness and fatigue. Methods Fourteen professional female field hockey players (age: 20.4 ± 5.4 years; body mass: 60.7 ± 7.2 kg; height: 167.0 ± 1.0 cm) volunteered to participate in this investigation. Maximal isometric hip adductor and abductor strength were obtained before (pre-match 1) and after the first match (post-match 1), after the second match (post-match 2), and 48 h after the second match. Locomotion patterns during the matches were obtained with portable Global Positioning System (GPS) and perceived exertion (RPE) was assessed after each match. In addition, Wellness Questionnaire (5-WQ) and the Total Quality Recovery Scale (TQR) were employed before the matches and 48 h after the second match. Results For the non-dominant limb, the maximal isometric hip adductor and abductor strength were lower after post-match 2 when compared to pre-match 1 (p = 0.011). Hip abductor strength in the non-dominant limb remained reduced 48 h after post-match 2 (p < 0.001). There were no differences in the total distance covered when comparing match 1 and match 2. Players reported more acute fatigue (5-WQ, p = 0.009) and increased muscle soreness on pre-match 2 compared to pre-match 1 (p = 0.015), while fatigue returned to pre-competition levels 48 h after post-match 2 (p = 0.027). No changes were observed in the TQR. Conclusion The assessment of maximal adductor and abductor strength before and after competitive matches, in addition to evaluating self-perceived fatigue by a wellness questionnaire can help to identify field hockey players with excessive fatigue responses during tournaments with a congested match program.